The crystal city - Card, Orson Scott (New York: Tor, 2003)
A fantasy set in nineteenth-century America, this sixth novel of the Alvin Maker series follows the magical leader as he leads a massive band of slaves, Cajuns, and displaced persons on an exodus to freedom.
Maps on lining pages.
Accelerated Reader AR
Keywords: Maker, Alvin (Fictitious character) -- Fiction; Fantasy fiction